2012
DOI: 10.1029/2011wr011501
|View full text |Cite
|
Sign up to set email alerts
|

Improved methods for daily streamflow estimates at ungauged sites

Abstract: [1] In this paper, improved flow duration curve (FDC) and area ratio (AR) based methods are developed to obtain better daily streamflow estimation at ungauged sites. A regression based logarithmic interpolation method which makes no assumption on the distribution or shape of a FDC is introduced in this paper to estimate regional FDCs. The estimated FDC is combined with a spatial interpolation algorithm to obtain daily streamflow estimates. Multiple source sites based AR methods, especially the geographical dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 33 publications
0
116
0
Order By: Relevance
“…Related hydrological studies also suggested that the number of donor catchments required to improve hydrological model performance at ungauged catchments varies from 5 to 10 (e.g. McIntyre et al 2005, Oudin et al 2008, Zhang and Chiew 2009, Patil and Stieglitz 2011, Shu and Ouarda 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Related hydrological studies also suggested that the number of donor catchments required to improve hydrological model performance at ungauged catchments varies from 5 to 10 (e.g. McIntyre et al 2005, Oudin et al 2008, Zhang and Chiew 2009, Patil and Stieglitz 2011, Shu and Ouarda 2012.…”
Section: Discussionmentioning
confidence: 99%
“…It is apparent that the semi-distributed model provides the most trustworthy results due to its better performance. Shu and Ouarda (2012) recommended at least four streamflow observations as donor variables for good precision with the FDC methods. Thus, the regional FDC with two streamflows and I CP in this study could add more uncertainty than a case with more donor variables.…”
Section: Regional Fdc Methods For Regulated Watershedsmentioning
confidence: 99%
“…Thus, one or multiple donor variables close to the target station have been typically used in the regional FDC approaches. Shu and Ouarda (2012) suggested using multiple donor variables to minimize the uncertainty of using a single donor variable. This study used two sets of neighboring streamflow observations as well as I CP to generate streamflows in sub-watersheds.…”
Section: Regional Fdc For Regulated Watershedsmentioning
confidence: 99%
See 2 more Smart Citations